Construction of individual training with athletes 9-11 years in the ice dancing - Артем’єва [Galina Artem’yeva] Галина Павлівна; Муллагільдіна [Alla Mullagіldіna] Алла Ядікакарівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Analyzed the mistakes in the fundamental technology of ice skaters 9–11 years old. Anaerobic working capacity has been determined using the 60-second hopping test method the level of special physical training has been revealed. Strong correlations indicators by type of fitness have been established identified compliance ratings athletes on the technical readiness and anaerobic power. By the Content and direction of individual pairs of athletic training program are justified for the development of qualification of candidates for the master of sports. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>